Pengaruh Kompensasi, Lingkungan Kerja Dan Kepuasan Kerja Terhadap Turnover Karyawan PT. Tamarin Jaya Lombok Timur - Wiwik Ilnia; Syaiful Amri; Baiq Desthania Prathama (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2023)
This study aims to examine the effect of compensation, work environment and job satisfaction on employee turnover. This type of research is associative. Samples were taken using saturated sampling. Data was obtained by distributing 42 questionnaires to employees of PT. Tamarin Jaya East Lombok Branch. Data analysis using multiple linear regression showed (Y = 25.820 - 0.289x1 - 0.487x2 - 0.032x3). The results of this study show that compensation does not have a partially significant effect on turnover with a t value of -1.417 < t table 2.024 with a significant value of 0.165 > 0.05, the work environment has a partially significant effect on turnover with a t value of -2.770 < t table 2.024 with a significant value of 0.009 < 0.05, and job satisfaction has no partial significant effect on turnover with a calculated t value of -0.253 < t table 2.024 with a significant value of 0.801 > 0.05. Simultaneously there is an influence between compensation variables, work environment and job satisfaction on turnover with a calculated f value of 42.940 > f table 2.85.